The learning of science and mathematics in English among lower secondary pupils in the district of Klang / Siti Azura Khalid - Khalid, Siti Azura (2008)
The implementation of the policy of teaching Science and Mathematics in English was introduced to Year One, Form One and Form Six pupils in all schools in Malaysia beginning 2003. This move was expected to provide opportunities for pupils to use English language and it was intended to increase their proficiency in the language. In view of this, the purpose of this research was to assess pupils’ readiness of learning Science and Mathematics in English after five years of its implementation from the perspective of pupils. A total of 507 pupils, from the levels of Form One and Form Two, ages ranging from 13 to 14 years, participated in this study. The methodology used was quantitative in nature where a set of questionnaire and two sets of diagnostics tests for Form One and Form Two pupils respectively were used in measuring pupils’ readiness in the learning of Science and Mathematics in English. The results in term of pupils’ perceptions from the questionnaire indicate that both Form One and Form Two pupils have a positive perception toward the learning of Science and Mathematics in English. Approximately two-third of the pupils indicated their desire to continue on this policy that consists of a higher percentage of Form Two pupils than Form One pupils. Similarly, a higher percentage of pupils enjoy learning Mathematics than learning Science in English. The second part of the questionnaire was to measure pupils’ linguistic competency which was based on their understanding on spoken understanding of English texts, writing in English, speaking in English and confidence in speaking in English. The data suggests that the highest increment in Form One pupils and Form Two pupils’ linguistic improvement is in understanding spoken English. Form Two pupils rated higher confidence ability on the linguistic areas of competencies as compared to Form One pupils and significant difference was found only in the area of listening skills and reading skills. In the second part of this study, two separate diagnostic tests for each Form were used to diagnose pupils understanding of Science and Mathematics learning. Pupils’ achievements were based on the ten constructs and through the diagnostic tests pupils level of proficiency and understanding were assessed. The overall achievement score obtained for both tests was statistically significant. Form One pupils was found to have a higher level of difficulty in Science learning as compared to Mathematics learning in the English Language. For both diagnostic tests, the highest level of difficulty was in the construct of Expressing Science and Mathematical idea or information in English. The results from the diagnostic study reveals that pupils in schools are actually still facing language problems as well as content problems in learning Science and Mathematics and to overcome these problems they need help and guidance from the teachers. The result of this study indicates most pupils perceive the learning of Science and Mathematics in English has brought positive effects especially in terms of language skills based on pupils’ perception on their linguistic performance in terms of their linguistic competencies.